First-Principles Guided Design of Pd-Decorated V2O5/Porous Silicon Composites for High-Performance NO2 Sensing at Room Temperature - Xiaoyong Qiang; Yongliang Guo; Zhipeng Wang; Tao Chen; Rui Zhang; Weibin Zhou (Nanomaterials)
A Pd-decorated V2O5/porous silicon (Pd-V2O5/PSi) composite was synthesized via magnetron sputtering for enhanced NO2 gas sensing. The material’s morphology and composition were systematically characterized, and its gas sensing performance was evaluated through comprehensive experimental measurements and first-principles calculations. The decoration of Pd nanoparticles significantly improved the sensing capabilities of the V2O5/PSi composite, particularly enhancing sensitivity and response/recovery characteristics. Experimental results revealed a 3.1-fold increase in response to specific NO2 concentrations (ppm level) compared to the undecorated V2O5/PSi sensor. The composite exhibited rapid NO2 response at room temperature with excellent selectivity, reproducibility, and long-term stability. First-principles calculations elucidated the structural, electronic, and adsorption properties of the Pd-V2O5/PSi composite, uncovering the gas sensing mechanism in NO2 environments. This combined experimental and theoretical study provides valuable insights for developing advanced gas sensors and lays a foundation for optimizing metal oxide-based sensing materials.